The Text of the Attorney General's Speech - Biddle, Francis (1942)
Clipping of Francis Beverley Biddle's (1886-1968) speech regarding Italian immigrants being 'Enemy Aliens'. During World War II Japanese, German, and Italian nationals were classified as enemy aliens in the United States. Enemy aliens were detained, denied citizenship, and deported. In 1942 Francis Biddle, the Attorney General of the United States, would no longer classify Italians as enemy aliens.
Keywords: Immigrants; Noncitizens; World War (1939-1945); Italians; Italian Americans; Biddle, Francis, 1886-1968; Newspapers; Clippings (Books, newspapers, etc.)